Construcción de un banco de pruebas para realizar ensayos Jominy de templabilidad en aceros aleados para la Universidad Antonio Nariño - Sede Neiva (2023)
In this proposed project a Jominy test bench for steel hardenability is built, for the universidad Antonio Nariño, sede Neiva, Mechanical Engineering program. The machine design chosen is alternative three (Banco de pruebas ensayo Jominy con accionamientos manuales). This is under the principle of a hydraulic system and other parameters that comply with what is described in the ASTM A255 standard. The Jominy test was carried out step by step on the parts, in addition to which they were subjected to a hardness measurement, applying methods called Leeb hardness (HL) and Rockwell hardness C (HRC), obtaining values with ranges between 56 - 11 (HRC) steel SAE 1045 and 59 - 16 (HRC) SAE 4140 alloy steel, allowing to be compared thanks to the hardenability curves. Finally, a laboratory guide and a maintenance manual were elaborated, which will be of use and help to the students.